Anticipation and Prioritization of Green Jobs in Iran Using a Multi-Criteria Decision Analysis Method - Abbas Karimi; Majid Namdari; Seyed Saeid Mohtasebi; Mahmoud Salimi (Environmental Energy and Economic Research, 2022)
The green economy is defined as an economy that aims at reducing environmental risks and ecological scarcities, and that aims for sustainable development without degrading the environment. This new economy will lead to the creation of new jobs, thus improving community health and providing opportunities for sustainable wealth and value creation. The paper aimed to study and anticipate the future skill needs for the green economy. Research population was the whole Iran. Data gathering was done in two phases, first by using both interview and questionnaire for 5 related chief experts and second one by using only questionnaire for 61 specialist and experts as the research sample. The primary results showed 604 green skills and jobs for Iran. Finally, 102 jobs were identified as the future green jobs during 3 steps. These were prioritized from 1st rank to 102nd rank by using TOPSIS, 35 green jobs in group 1 (high ranks), 35 green jobs in group 2 (medium ranks) and 32 green jobs in group 3 (low ranks). The results showed the important consideration about training and education in the field of green jobs. One of the biggest challenges facing the green economy is shortage of skillful labor force. Considering the results of this study and using other potential resources in Iran in the field of green jobs, Iran Technical and Vocational Training Organization as an establishment responsible for skill training shall take essential steps to get the green economy.